Debt/credit, money and social relationships in the underground credit markets of Soweto, South Africa - Krige, Detlev (Social Science Information)
This article engages with contemporary debates about debt and money from the vantage point of an ethnographic study of unregulated, small-scale moneylending business who continues to operate in the township of Soweto$1 (Bs poorer neighbourhoods. Following Peebles$1 (Bargument that reading poor people$1 (Bs unwillingness to bank with formal institutions as a sign of ignorance is unwarranted, this article describes persistent dynamics of underground credit markets and personalized credit relationships, demonstrating how the practice of ukumashonisa (extending cash money as credit) by neighbourhood lenders are embedded in social fields shared by lenders and borrowers. This article further demonstrates how the vilification of the figure of the township moneylender (mashonisa) by a broad coalition of civil society groups, trade unions, the state and commercial financial institutions, assisted in the financialization of poor people$1 (Bs monies. This public consensus about the depravity of the neighbourhood moneylender is not shared by all Sowetans, especially poor and unemployed Sowetans who have been pushed into a greater dependency on both money and intense personalized social relationships as they try to survive. Seeking out personalized credit relationships, and turning debt transactions, contracts and relationships with local moneylenders into exchanges that take on the appearance of gifts rather than commodity exchanges, continues to remain a strategy for people who are no longer able to count on stable wage work as their primary source of income. - Reproduced.s
Keywords: Credit; Money; Credit markets - South Africa